Stereoselective Synthesis of Indanylglycine Derivatives by a Tandem Michael–Michael Reaction - Rincón, Ángela; Carmona, Vanesa; Torres, M. Rosario; Csákÿ, Aurelio G. (Synlett, 2012)
The construction of 1,2,3-trisubstituted indane rings by the Michael addition of a glycinate followed by an intramolecular Michael cyclization is reported. The tandem process affords indanylglycine derivatives with high regio- and diastereoselectivity.
Keywords: amino acids; carbanions; carbocycles; Michael addition; tandem reaction